The Implementation of Online English Learning During The Covid-19 Pandemic - Luluk Setyowati; Helda Jolanda Pentury; Anastasia Dewi Anggraeni (STKIP PGRI Lubuklinggau, 2022)
The COVID-19 pandemic has had a very significant impact on human life. Various aspects of life are affected, including the realm of education which has turned online and has various impacts on the level of success in its implementation. This study aims to see how the implementation of online English learning during the pandemic. There are various problems including, some students lack facilities to support their online learning; It is difficult for teachers to get grades and catch up with student assignments which are hampered by various facilities constraints; the lack of sensitivity of parents to their important role in every online learning activity and the difficulty of achieving learning goals which are limited to essential materials only. Based on the results of the study, the solution to this problem is to collect assignments offline, provide understanding to parents of students about the importance of mentoring and allocation of aid funds in schools to help students who lack facilities.